Use of Modern Technologies in the Process of Product Development/Production Process (Vloga naprednih tehnologij v inženiringu poslovnih sistemov, 2025)
The demand for new products, which are also increasingly complex, is constantly growing and companies must respond to this demand by developing and producing the right products at the right time and at a price that is affordable enough to maintain their competitive advantage. While new product development inevitably involves risks, these can be mitigated by using one of the reference models for managing new product development activities. To this end, in this section we provide an overview of the development of reference models for new product development. In the following section, we focus on the introduction of modern technologies that are increasingly being integrated by companies into the new product development process. The main goal of integrating advanced technologies is to reduce the time and costs associated with new product development. We introduce the purpose of integrating advanced technologies and provide an overview of the challenges companies face and the benefits they can achieve.